Income Inequality of West Java Province and the Factors That Affect It - Sri Rahayu Ningsih; Eni Setyowati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Income inequality is one of the indicators to see the magnitude of the difference in economic growth in an area with the difference in existing resources making an area can be said to be advanced and underdeveloped, so it can lead to weakening of social stability, economic inefficiency and solidarity. West Java province is the province that has the fourth highest level of inequality out of seven provinces in 2020. This study aims to analyze the amount of income inequality in West Java province with several variables that have been selected, namely: minimum wage; open unemployment rate, poor population, government spending. The data source used comes from the Central Statistics Agency of West Java province. In this study using Theil entropy index analysis method and panel data regression. The model chosen in this study is the Fixed Effect Model (FEM) of the model is known that only the minimum wage open unemployment rate and the poor have a significant effect on income inequality in West Java province in 2017-2020.